1991
DOI: 10.3758/bf03212174
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual order and the effect of vocalic context on fricative perception

Abstract: This three-part study demonstrates that perceptual order can influence the integration of acoustic speech cues. In Experiment 1, the subjects labeled the lsl and If] in natural FV and VF syllables in which the frication was replaced with synthetic stimuli. Responses to these "hybrid" stimuli were influenced by cues in the vocalic segment as well as by the synthetic frication. However, the influence of the preceding vocalic cues was considerably weaker than was that of the following vocalic cues. Experiment 2 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
2
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 39 publications
2
31
2
1
Order By: Relevance
“…Mann and Soli (1991) showed that adults assign little weight to acoustic properties within the vocalic portion of the syllable when the fricative follows, rather than precedes, the vowel. We wished to determine whether children would show a similar decrease in perceptual attention to attributes of the vocalic portion of the syllable when the fricative came at the end of the syllable, rather than at the beginning.…”
Section: Experiments 1 Original Ordermentioning
confidence: 99%
See 2 more Smart Citations
“…Mann and Soli (1991) showed that adults assign little weight to acoustic properties within the vocalic portion of the syllable when the fricative follows, rather than precedes, the vowel. We wished to determine whether children would show a similar decrease in perceptual attention to attributes of the vocalic portion of the syllable when the fricative came at the end of the syllable, rather than at the beginning.…”
Section: Experiments 1 Original Ordermentioning
confidence: 99%
“…In another examination of the flexibility of adults' perceptual strategies for speech, Mann and Soli (1991) investigated changes in adults' weighting strategies in which there was dependence on the order of segments within the syllable. They found that adults paid less attention (assigned low weights) to both vocalic formant transition and to vowel quality in decisions offricative identity when the fricative came after the vowel (i.e., syllablefinal position), rather than before (i.e., syllable-initial position).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…E-mail: holger.mitterer@mpi.nl or james.mcqueen@mpi.nl context (see, e.g., Fowler, 2005;Fowler, Best, & McRoberts, 1990;Fowler & Brown, 2000;Kingston & Macmillan, 1995;Lindblom & Studdert-Kennedy, 1967;Mann, 1980;Mann & Repp, 1980, 1981Mann & Soli, 1991;Mitterer, 2006b;Smits, 2001a). Once again, there are multiple theoretical variants of this view.…”
mentioning
confidence: 99%
“…Perceivers perceptually "compensated" for the coarticulatory effects of the nasal consonant on the preceding vowel by attributing acoustic information from one segment to the following segment. Research has identified a range of contexts in which CFC effects occur (e.g., Mann and Repp, 1980;Repp and Mann, 1981;Mann and Soli, 1991;Lotto and Kluender, 1998;Elman and McClelland, 1988;Mitterer and Blomert, 2003;Fowler, 2006), including synthesized, natural, and even non-speech contexts.…”
Section: Introductionmentioning
confidence: 99%